2015
DOI: 10.1002/2015wr017810
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic fracturing fluid migration in the subsurface: A review and expanded modeling results

Abstract: Understanding the transport of hydraulic fracturing (HF) fluid that is injected into the deep subsurface for shale gas extraction is important to ensure that shallow drinking water aquifers are not contaminated. Topographically driven flow, overpressured shale reservoirs, permeable pathways such as faults or leaky wellbores, the increased formation pressure due to HF fluid injection, and the density contrast of the HF fluid to the surrounding brine can encourage upward HF fluid migration. In contrast, the very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 73 publications
3
113
0
1
Order By: Relevance
“…Although the total number of cases of thermogenic stray gas is relatively low, it is clear from COGCC complaint reports that individual cases pose significant safety, financial, emotional, and health risks to landowners (SI Appendix). Evaluation, mitigation, and prevention of these impacts should remain an ongoing high priority (32,39,40).…”
Section: Resultsmentioning
confidence: 99%
“…Although the total number of cases of thermogenic stray gas is relatively low, it is clear from COGCC complaint reports that individual cases pose significant safety, financial, emotional, and health risks to landowners (SI Appendix). Evaluation, mitigation, and prevention of these impacts should remain an ongoing high priority (32,39,40).…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of the impacts of unconventional O&G development on groundwater quality is difficult to assess as the requirement for monitoring groundwater near O&G well pads was just recently introduced in very few jurisdictions. Reports of incidents are mostly restricted to surface operations, and there are few reports of incidents leading to subsurface impacts . Long et al (2015) have concluded that direct impacts of fracking appear small but have not been investigated, and Jackson et al (2013) have advocated for field‐based research to fill the knowledge gap.…”
Section: Groundwater Quality Risks Related To Shale Gas Developmentmentioning
confidence: 99%
“…The study of multiphase flow in porous rocks is related to a broad field with important challenges [ Bruce and Klute , ; Richards , ; Sahimi , ; Singh , ; Washburn , ]. The investigation of water imbibition in porous rocks is important in a variety of contexts, including the recovery of hydrocarbons from ultralow permeability reservoirs [ Akin and Kovscek , ; Karpyn et al ., ; Li and Horne , , ], the disposal of nuclear waste [ Hunt and Tompson , ; Sahimi , ; Tompson et al ., ], the sequestration of CO 2 [ Doster et al ., ; Herring et al ., ], the environmental remediation [ Faybishenko et al ., ], and the protection of buildings and groundwater [ Birdsell et al ., ; Cheng et al ., ; Hall and Hoff , ]. Several nondestructive techniques [ Roels et al ., ], including nuclear magnetic resonance (NMR) or magnetic resonance imaging (MRI) [ Carpenter et al ., ; Leech et al ., ; Pohlmeier et al ., ] and Îł ray attenuation [ Ferguson and Gardner , ; Nielsen , ; Nizovtsev et al ., ], have been applied to probe distributions of water saturation and to study the dynamics of liquid transport in porous materials.…”
Section: Introductionmentioning
confidence: 99%